Improving Science Process Skills Class Xi Ipa 1 Man 3 Banjarmasin Inquiry Discovery Learning (IDL) Guided By Operation Of Model Material In Teaching Impulse And Momentum - Lisda Karmila; Zainuddin Zainuddin; Syubhan An'nur (Universitas Lambung Mangkurat, 2014)
Teacher’s teaching methods that are conventional to be one of the causes of low student science process skills, to do research that aims to determine the effectiveness of the model applies the IDLguided in improving student’s science process skills. The specific aims of this study were to describe: (1) feasibility RPP, (2) student’s science process skills, (3) student learning outcomes, (4) the response of students towards learning. The research method is action research. The subjects were 39 students of class XI IPA 1 MAN 3 Banjarmasin. Data collection techniques used observation, achievement test, questionnaire, and documentation. Descriptive data analysis techniques of qualitative and quantitative descriptive. The findings of the study are (1) RPP feasibility in the first cycle by 73,68%, 84,87% for the second cycle and third cycle of 92,11% (2) student’s science process skills include doing experiments properly, write down observations, analyzed the data, and make conclusions. In general, the first and second cycle has criteria pretty good, and the increase in cycle III with both criteria (3) student learning outcomes in the classical increase of 67,57% (still incomplete) in the first cycle, to 87,18% (complete) on cycle II, and 100% (complete) in the third cycle (4) the response of students towards learning generally categorized either. The conclusion of this research is the application of the IDL-guided effective in improving student’s science process skills class XI IPA 1 MAN 3 Banjarmasin on impulse and momentum teaching materials.